Determination of some quality properties of "hamsi kaygana" prepared with different additives. Issue 2 (12th January 2018) - Taşkaya, Latif; Yaşar, Elif
Abstract: This study was aimed to determine the changes of the local anchovy meal which is known as hamsi kaygana in Turkey during cold storage at +4°C ± 1°C. Physicochemical (pH, TVB‐N, TMA‐N, and TBA) shelf life analyses were carried out for hamsi kaygana samples. It was confirmed that the pH values obtained from research groups were within the limit values of the literature. No statistically significant difference was observed ( p  > .05) between control, stinging nettle, and rosemary groups that were within all created product groups on 12th day of storage, and the observed difference was only present in cumin group ( p  < .05). Upon examining TVB‐N (Total Volatile Basic Nitrogen) values on 12th day of storage, we saw the lowest TVB‐N value (17.01 ± 0.21 mg/100 g) was at stinging nettle group. However; it was found out that highest TVB‐N value belonged to cumin group with the value of 19.38 ± 0.42 mg/100 g. It was found that 12th day TBA (Thiobarbituric Acid) values of all other groups except control group did not exceed limit values. Among TMA‐N (Trimethylamine Nitrogen) values of all groups on 12th storage period, the lowest value belonged to cumin group samples. While the highest TMA‐N value was found as 14.70 ± 0.30 in control group samples. Therefore, the results showed us that using dried herb and spices in hamsi kaygana production and the storage of the products have an influence on shelf life. Abstract : This study aimed to determine the effect of dried stinging nettle, rosemary and cumin on the meat quality and shelf life of hamsi kaygana, a traditional food in the Black Sea Region of Turkey. The study groups consist of the control group, stinging nettle, rosemary and cumin. The effects of dried herb and spices on shelf life and quality of cooked hamsi kaygana which is stored in refrigerator conditions (4°C ± 1°C). At the end of the storage period, the pH value showed an increase in all groups compared to the initial value and was determined to be 6.30 ± 0.01, 6.32 ± 0.04, 6.32 ± 0.00 and 6.31 ± 0.02 for groups control, stinging nettle, rosemary and cumin respectively. It was found out that pH values obtained from the groups were within limit values of the literature. On the last day of the storage, the cumin group had the highest TVB‐ N value of 19.38 ± 0.42 mg/100. According to the TVB‐N analysis results obtained on the final day of storage, it was seen that all groups remained within acceptable limits. As a result of the study, other groups apart from the control group did not exceed the threshold values for TBA on 12th day. It was found that the rosemary group had the lowest TBA value (5.85 ± 0.37 mg·MDA/kg) on the 12th day of storage of all groups. TMA‐N value of stinging nettle group at the beginning was measured as 2.90 ± 0.17, it was found that this value was approximately seven times more (13.50 ± 0.30) than the value at the beginning on 12th day. It was seen that the value measured exceeded the spoilage value of TMA‐N. First TMA‐N value of the group containing rosemary was found to be 3.30 ± 0.00 mg/100 g before storage. On the 8th day of storage, a TMA‐N value was found as 9.90 ± 0.30 mg/100 g which is a rapid increase with three times more than the first value. The TMA‐ N values increased in all groups and the highest increase was observed in the control group (14.70 ± 0.30 mg/100 g) on the 12th day of storage. The lowest TMA‐ N value (12.90 ± 0.30 mg/100 g) was obtained in the cumin group at the end of the storage day. It was found that the cumin used in the production is much more effective than the stinging nettle (13.50 ± 0.30 mg/100 g) and rosemary (14.40 ± 0.00 mg/100 g) in terms of product shelf life. According to results obtained, the effects of dried herbs and spices which are used in the production of hamsi kaygana on the storage of products were examined. As a result of the study conducted, the importance of the alternative consumable food product, which is obtained from anchovy which has a high potential of consumption in our country, pointed out.